Çarpanlara Ayırma

                   2                      2

     1)  (x - y)   = (y - x)

          

             2              2
     2)  x    -   y    = (x - y).(x + y)
                                  2          2                       2   

     3)  ( x + y )   = x   - 2xy + y

 

                     2           2                         2   

     4)  ( x - y )   = x   + 2xy + y

                                        2           2     2      2

     5)  ( x + y - z )   = x +y + z   +2(xy - xz - yz)

 

            2                                     2         2

     6)  x   +2y = (x  +   y)   - y

                      3        3           2                  2          3 

     7)  ( x + y ) = x  + 3x  y + 3xy   + y

                     3       3         2                2         3 

     8)  ( x - y ) = x - 3x y + 3xy   - y

                 3       3                            2                  2

     9) x  - y = ( x - y ). (x + xy + y )

                 3     3                     3          

   10) x - y  = ( x - y ) + 3xy.(x - y)

           3      3                               2                2

   11) x + y = ( x + y). ( x - xy + y )

           3       3                    3               

   12) x + y = ( x + y) – 3xy.(x + y)